Método de ponto proximal para problemas de equilíbrio em espaços de Hilbert - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
In this dissertation, we present a proximal point method for solving problems balance in Hilbert spaces proposed by Alfredo Iusem and Wilfredo Sosa in [1]. We analyzed the convergence of this mehtod for troubleshooting balance. We verified the sequence generated by the method of classical proximal point and generated sequence the proximal point method to balance problems are the same. These results were obtained using variations of monotonicity of the function that defines the balance problem. In the final analysis is made on the weakening of the hypothesis assumed by function.
Keywords: Problema de equilíbrio; Método de ponto proximal; Reformução de problemas de equilíbrio; Equilibrium problem; Proximal point method; Reformulation of equilibrium problems; Variações de monotonicidade; Espaços de Hilbert; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA